PENERAPAN FUZZY ANALYTIC NETWORK PROCESS (FANP) UNTUK PENENTUAN PRIORITAS KRITERIA PADA PEMILIHAN MAHASISWA BERPRESTASI DI UNESA - Adiliya Romadhayu; Yuliani Puji Astuti (Universitas Negeri Surabaya, 2020)
The selection of outstanding students needs to be done at each university, so that the potential possessed by students in the form of hard skills and soft skills can be increased and the achievements obtained are better. Hard skills and soft skills can be developed by the students participate in various activities that have been made by the department, faculty, and campus. Outstanding students mentioned in this regard should have a good performance in academic and non academic. In the Achievement Student Selection (Pilmapres) there are several criteria that must be met. To determine the priority criteria that influence in this Pilmapres it is necessary to calculate the weight of each criterion. In this study the Fuzzy Analytic Network Process (FANP) method is used. Fuzzy Analytic Network Process (FANP) method is a combination of fuzzy method and Analytic Network Process (ANP) method. By using the FANP method it can be seen that the criteria which are very influential are the criteria for the achievement of field competition where the weight is 22%, the award rate criteria is 17,9%, the weighting criteria for the superior performance results is 14,1%, the weighting criteria for the superior performance award is 11,9%, the weighting of the role criteria in the superior achievements was 11,6%, the weighting of the registrant identity criteria was 10,9%, and the weighting of the career criteria in the organization was 7,6%. For the sub-criteria that influence in the Pilmapres, among others, are innovative findings which have a weight of 27,6%, a work subcriteria 26,9% and a product subcriteria 25,6%.